PELAKSANAAN BAURAN PROMOSI TIKET PENERBANGAN PADA PT. FANTASTIK TOUR & TRAVEL KOTA BATAM PROVINSI KEPULAUAN RIAU - Jalil, Fitri Yelisa; Yusrizal, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Promotion is one of important factor which have to be in a program at a company for introducing their product in to people. Including the companies engaged in tourism industry that spread throughout Indonesia. Batam is one of cities in Indonesia that has many companies engaged in tourism indutry because of the location near by neighbouring countries like Singapore and Malaysia. One of that company is PT. Fantastik Tour & Travel who has been in business since 2004. In development of the company, PT. Fantastik Tour & Travel carried out several promotion programs. This research aims to find out what promotion that has been carried out by PT. Fantastik Tour & Travel and how to carry out the promotion with promotion mix as a concept. Data of this rearch was obatained from observation, interviews, and documentation, with data collection techniques using key informant purposive sampling. Based in this research, explain about what promotion mix that carry out by PT. Fantastik Tour & Travel to promote their flight ticket product and how to carry out that promotion mix according to communication tools of promotion mix.Keywords: Promotion Mix, Tour & Travel, Flight Ticket